Utilization of dental services among secondary school students in Port Harcourt, Nigeria - Eigbobo, Joycelyn Odegua; Obiajunwa, Chinonso Claude (European Journal of General Dentistry, 2016)
Background: Regular use of dental services has been associated with optimal oral health. Reports in some parts of Nigeria have shown the poor utilization of dental services, but there is a paucity of information relating to oral health care seeking behavior in the South-South region of Nigeria. Aim: To determine the pattern of utilization and identify barriers to utilization of dental services among children. Materials and Methods: This was a cross-sectional study done among children aged 12-15 years in secondary schools in Port Harcourt, Nigeria. Information was elicited by means of a self-administered structured questionnaire. These included sociodemographic characteristics, views on dental visits, reported visits during the previous year, pattern of dental visits, and the barriers to utilization. Demographic variables and associations were tested using Chi-squared tests with the level of statistical significance set at P < 0.05 at 95% confidence interval. Results: There were 200 school children; 98 (49%) males and 102 (51%) females with a mean age of 13.3 (±1.1) years. Dental visits were deemed important by 187 (93.5%) children, and 32.0% respondents suggested that visits should be when there are symptoms. Only 42 (21%) pupils had been to the dentist in the last 12 months. The barriers to utilization of dental services majorly included no perceived needs (64.3%). Demographic variables had no significant association with reported visits and pattern of visits. Conclusion: Utilization of dental services among these school children was low and the major barrier was no perceived need. Oral health awareness needs to be improved on the importance of a regular checkup.
Keywords: Dental services; dental visits; Port Harcourt; school children